Shunt active filter for power quality improvement of SRM drive FED DG system - Suresh, Kavya; G, Nandan (International Journal of Engineering and Technology, 2018)
Electric power produced by the use of ordinary fuels will produce toxic gasses like carbon dioxide, carbon monoxide, nitrogen dioxide etc. Which will causes environment contamination and as a result cause to global warming. This bring to the use of renewable energy sources. A Solar Photovoltaic (SPV) system, along with Maximum Power Point Tracking (MPPT), catenated to a three phase grid which feeding a switched reluctance motor is introduced. The catenation of solar photovoltaic system to the grid arise through two stages of operations, which is through a DC/DC boost converter via a Voltage Source Inverter (VSI). The Maximum power point tracking algorithm used is Perturb & Observe (P &O) algorithm, which is applied to the boost converter. Also reference reimbursement current has been generated by using I cos Î¦ algorithm. Adaptive hysteresis band current controller is used for switching pulse generation in current controlled VSI. Em-ploying adaptive control, the Total Harmonic Distortion (THD) of supply current is reduced to 0.22% from 28.20%. There by the power factor is increased to a value 0.976%.Â Â